Problems of Social Studies Learning at Elementary Education Level: What are the Recommended Solutions? - Saidah, Karimatus; Damariswara, Rian (Universitas Nusantara PGRI Kediri, 2024)
This study aims to examine the problems of implementing social studies learning at the elementary education level and describe the recommended solutions to the problems faced based on previous studies. The method used in this study is a literature study by collecting articles that are in accordance with the study and reducing and analyzing the data obtained to then draw conclusions based on the studies that have been conducted. The results of the study indicate that there are several problems faced in the implementation of social studies learning, including the implementation of social studies learning that has not been truly integrated, low student interest in learning social studies and inaccuracy in selecting social studies learning strategies. Recommendations for social studies learning that can be done are to implement contextual-based social studies learning, namely teaching social studies by linking it to students' social lives, so that students can feel the connection between social studies learning and everyday life.